A rare case of protein C mutation causing neonatal purpura fulminans - Tawab, Abdul; George, Madhu; Joseph, Jino; Zacharias, Ann Mary (International Journal of Contemporary Pediatrics, 2021)
Congenital protein C deficiency presenting as purpura fulminans is a rare condition in neonates. It is a disorder with autosomal recessive inheritance and is caused by homozygous or compound heterozygous mutations in PROC gene. The authors report a case of autosomal homozygous PROC gene transversion mutation in a newborn baby born to third degree consanguineous parents who presented as purpura fulminans at birth. She had almost undetectable protein C levels. As protein C concentrate was not readily available, she was managed with low molecular weight heparin along with fresh frozen plasma. Despite our best efforts, baby succumbed to her illness on day 21 of life. Autosomal recessive protein C deficiency should always be sought as an explanation for thrombotic disorders in the newborn with manifestations of disseminated intravascular coagulation.